2004
DOI: 10.1088/1478-3967/1/2/p01
|View full text |Cite
|
Sign up to set email alerts
|

Physical schemata underlying biological pattern formation—examples, issues and strategies

Abstract: Biological systems excel at building spatial structures on scales ranging from nanometers to kilometers and exhibit temporal patterning from milliseconds to years. One approach that nature has taken to accomplish this relies on the harnessing of pattern-forming processes of non-equilibrium physics and chemistry. For these systems, the study of biological pattern formation starts with placing a biological phenomenon of interest within the context of the proper pattern-formation schema and then focusing on the w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 24 publications
(21 reference statements)
2
41
0
Order By: Relevance
“…Common features displayed by these self-organized phenomena are the formation of trails that lead to the emergence of dramatic patterns of large-scale order (15). The processes leading to pattern formation in biological systems are likely to be more complex than the spontaneous emergence of patterns that are observed in nonliving systems and will involve an interplay of physical, chemical, and biological parameters (16,17).…”
mentioning
confidence: 99%
“…Common features displayed by these self-organized phenomena are the formation of trails that lead to the emergence of dramatic patterns of large-scale order (15). The processes leading to pattern formation in biological systems are likely to be more complex than the spontaneous emergence of patterns that are observed in nonliving systems and will involve an interplay of physical, chemical, and biological parameters (16,17).…”
mentioning
confidence: 99%
“…It has been suggested that there may be significant benefit in such collective community-level behavior and that such organism aggregations behave with a remarkable degree of plasticity and adaptability that allows them enhanced capability to meet changing and challenging growth conditions [20]. Obviously such plasticity with respect to the environment would be particularly pertinent to extremophile organisms living in an array of especially challenging physical and chemical conditions.…”
Section: Extremophilesmentioning
confidence: 99%
“…Materials exhibiting such properties (though not typically all at once) also exist outside biology, where they are known as 'soft matter' [6] and 'excitable media' [7,8].…”
Section: Introductionmentioning
confidence: 99%